Basic life support, a necessary inclusion in the medical curriculum: a cross‑sectional survey of knowledge and attitude in Uganda - Ssewante, Nelson; Wekha, Godfrey; Musoke, Phillip; Nabukeera, Germinah; Kamuhangire, Lauben; Tagg, Andrew (BMC medical education, 2022)
Uganda continues to depend on a health system without a well-defined emergency response system. This is in the face of the rising cases of out-of-hospital cardiac arrest contributed largely to the high incidence of road traffic accidents. Non-communicable diseases are also on the rise further increasing the incidence of cardiac arrest. Medical students are key players in the bid to strengthen the health system which warrants an assessment of their knowledge and attitude towards BLS inclusion in their study curriculum. A descriptive cross-sectional study was conducted in 2021 among undergraduate medical students across eight public and private universities in Uganda. An online-based questionnaire was developed using Google forms and distributed via identified WhatsApp groups. Chi-square or Fisher’s exact test and logistic regression were performed in STATA 15 to assess the association between knowledge of BLS and demographics. P < 0.05 was considered statistically significant. Out of the total 354 entries obtained, 351 were analyzed after eligibility screening. Of these, (n = 250, 71.2%) were male less than 25 years (n = 273, 77.8%). Less than half (n = 150, 42.7%) participants had undergone formal BLS training. Less than a third of participants (n = 103, 29.3%) had good knowledge (≥ 50%) with an overall score of 42.3 ± 12.4%. Age (p = 0.045), level of academic progress (p = 0.001), and prior BLS training (p = 0.033) were associated with good knowledge. Participants with prior training were more likely to have more BLS knowledge (aOR: 1.7, 95% CI: 1.1–2.7, p = 0.009). The majority (n = 348, 99.1%) believed that BLS was necessary and would wish (n = 343, 97.7%) to have it included in their curriculum. Undergraduate medical students have poor BLS knowledge but understand its importance. Institutions need to adopt practical teaching methods such as clinical exposures, field experience in collaboration with local implementers, and participating in community health promotion campaigns.